IFN-gamma protects short-term ovarian carcinoma cell lines from CTL lysis via a CD94/NKG2A-dependent mechanism. - Malmberg, K; Levitsky, V; Norell, H; de Matos, C; Carlsten, M; Schedvins, K; Rabbani, H; Moretta, A; Söderström, K; Levitskaya, J; Kiessling, R (2002)
IFN-gamma regulates the immunogenicity of target cells by increasing their expression of HLA class I molecules. This facilitates the T cell receptor-mediated recognition by CD8(+) T cells but decreases target cell sensitivity to lysis by NK cells due to engagement of inhibitory NK receptors. In this study, short-term tumor cell lines from patients with advanced ovarian carcinomas were established. We demonstrate the paradoxical finding that IFN-gamma treatment of these short-term ovarian carcinoma cell lines (OVACs) resulted in resistance of tumor cells to lysis by peptide- and allospecific CD8(+) T cells. Blocking experiments revealed that this phenomenon was dependent on enhanced inhibitory signalling via CD94/NKG2A receptors expressed on the effector cells. This was associated with increased expression of HLA-E mRNA and HLA-G at the protein level in IFN-gamma-treated OVACs. Furthermore, pulsing of untreated OVACs with the leader sequence peptide of HLA-G protected these cells from lysis by CTLs, thus mimicking the inhibitory effect of IFN-gamma. This study provides evidence that CD94/NKG2A receptors play an important role in regulating T cell activity against tumors and shows that IFN-gamma modulation of target cells may shift the balance of triggering and inhibitory signals to T cells, turning off their cytolytic activity.